Structural and spectral properties of a non-classical C58 isomer and its fluorinated derivatives in theory. Issue 3 (5th January 2021) - Song, Xiaoxi; Mao, Renfeng; Wang, Ziwei; Qi, Jiayuan
Abstract : The X-ray spectra have good isomer dependence and give a comprehensive insight of the electronic structure of the system. Abstract : The traditional classical fullerene is only composed of pentagons and hexagons, with many different topologies, of which only a few structures conform to the isolated pentagon rule (IPR), which means all five-membered rings are separated by hexagons, whereas isomers that violate the rule are called non-IPR isomers. In contrast, the non-classical fullerene consists of other kinds of polygons such as squares and heptagons in addition to pentagons and hexagons. X-ray photoelectron spectra (XPS), near-edge X-ray absorption fine structure (NEXAFS) spectra and X-ray emission spectra (XES), as well as the ground-state electronic/geometrical structures of the important non-IPR isomers C 3v - #1205 C58 and C 2 - #1078 C58, and the remarkable non-classical isomer C s -C58 (NC) with its two fluorides C s -C58 (NC)F18 (A) and C s -C58 (NC)F18 (B), have been computed at the density functional theory (DFT) level. Significant differences in the electronic structures and simulated X-ray spectra have been observed after fluorination. Meanwhile, strong isomer dependence has been shown in these spectra, which means the "fingerprint" in the X-ray spectra can effectively identify the above-mentioned fullerene isomers. As a consequence, the work can provide useful information especially isomer identification for experimental and theoretical research in fullerene science.